2000
DOI: 10.1001/jama.284.16.2112
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the US Health Care Safety Net

Abstract: ONTINUED INCREASES IN THE NUMBERS OF UNIN-sured US citizens, increasing premiums for those who are insured, and the debate over prescription drug coverage all have served to thrust the issue of access to health care on the national radar screen once again. Since the goal of universal health insurance seems less and less likely to be realized in the near future, much of the discussion has focused on the so-called safety net, which is the loosely knit health system that cares for those outside the traditional he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…1,2 Many believe that the growth in managed care, especially Medicaid managed care, threatens the viability of the safety net by leaving safety net providers with more uninsured patients, constraining their revenues and making them less willing to provide charity care. 1,[3][4][5][6] Increased hospital competition is believed to threaten the safety net by exerting fiscal pressures on hospitals and by lowering their ability to shift costs of charity care to insured patients Declines in public coverage are another factor cited as a threat. 1 Public insurance helps finance care provided by safety net providers and enhances their fiscal capacity to serve the low-income population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Many believe that the growth in managed care, especially Medicaid managed care, threatens the viability of the safety net by leaving safety net providers with more uninsured patients, constraining their revenues and making them less willing to provide charity care. 1,[3][4][5][6] Increased hospital competition is believed to threaten the safety net by exerting fiscal pressures on hospitals and by lowering their ability to shift costs of charity care to insured patients Declines in public coverage are another factor cited as a threat. 1 Public insurance helps finance care provided by safety net providers and enhances their fiscal capacity to serve the low-income population.…”
mentioning
confidence: 99%
“…1,5,7 Yet, there is little definitive information about the distribution of the safety net across communities, how it has changed over time, and what role changing market forces have played. There is evidence of substantial geographic variation in access for the uninsured, but whether this is the result of variation in the safety net is unknown.…”
mentioning
confidence: 99%
“…Lurie comments that "the safety net ideally should go beyond simply providing access to provide high-quality care to those it serves" and highlights the concerns over the ability of the safety net to meet the increasing demands of providing access to care and remain a viable entity. [ 12 ] In 2000, the Institute of Medicine identified three obstacles that providers within the safety net face: 1) the expanding numbers of uninsured persons; 2) the threat to the traditional sources of funding; and 3) the shift to Medicaid managed care. [ 12 , 13 ] Previous analysis has shown that visits to hospital outpatient departments are made by sicker patients with less continuity compared to physician's offices and community health centers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] In 2000, the Institute of Medicine identified three obstacles that providers within the safety net face: 1) the expanding numbers of uninsured persons; 2) the threat to the traditional sources of funding; and 3) the shift to Medicaid managed care. [ 12 , 13 ] Previous analysis has shown that visits to hospital outpatient departments are made by sicker patients with less continuity compared to physician's offices and community health centers. [ 5 ] Additionally, care at these sites is more likely to be provided by the practitioners less likely to be trained or experienced with high-risk patients, such as mid-levels or resident physicians.…”
Section: Discussionmentioning
confidence: 99%
“…2 Contributing factors include the growth of managed care and its use of enrollment caps, the erosion of subsidies used to finance the health care safety net, and increased demand for uncompensated care. 3 The last is particularly problematic given the increasing numbers of uninsured 4 and immigrant populations 5 and the disproportionately limited number of physicians in low-income areas. In addition, there has been a dramatic deterioration of state fiscal conditions over recent years 6 coupled with continuing increases in health care costs.…”
Section: Strains On the Safety Netmentioning
confidence: 99%